Prospective Christian Religious Education Teacher: Helping Students Find the Meaning of Life with Existentialism - Pays, Ordiana Martha; Kikhau, Resna Syarlina; Faot, Ormiaty; Ledoh, Novita Kridayanti; Pellokila, Ireni Irnawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
To become a Christian Religious Education (PAK) teacher candidate, they must have a strong understanding of theology and pedagogy, as well as the ability to help students find meaning in their personal contexts and lives. As a philosophy that emphasizes freedom, responsibility, and the search for meaning, existentialism can be a reflective approach to Christian education. In this article, we discuss how Christian Religious Education (PAK) teacher candidates can integrate the principles of existentialism with the values of Christian faith to help students answer fundamental questions about existence, purpose, and hope in life. PAK teachers are expected to be able to build a learning environment that encourages students to find the true meaning of life in the light of Christ by using approaches such as discussion, critical reflection, and faith experiences. This study emphasizes the importance of teachers helping people grow spiritually and existentially, so that Christian religious education is not only cognitive, but also transformational for students' lives.